2008
DOI: 10.1007/s11814-008-0176-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel soil stabilizer based on biodegradable poly(aspartic acid) hydrogel

Abstract: A novel soil stabilizer based on poly-amino acid -polyaspartic acid (PASP) and its copolymer which modified by xanthan gum (XG) was studied to increase soil particle compressive strength and resistance to wind erosion. Due to its unique property, the stabilizer aggregated individual soil particles and formed crust. The sample compressive strength increased from 0.175 to 0.612 MPa and the wind erosion modulus reduced from 22.43 to 10.56 g·m −2 ·min −1 after the 1% PASP hydrogel was applied by 1.67 Lm −2 (1 cm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The Any two means not sharing a common letter differ significantly at P ≤ 5% level findings of the study are supported by the earlier work done by Woodhouse and Johnson (1991) who also reported the improved emergence rate and percentage by soil treated with hydrogel. Yang et al (2008) studied a novel soil stabilizer based on poly-amino acid polyaspartic acid (PASP) and its copolymer which was modified with xanthan gum (XG) and concluded that the polymer had a positive influence on seed emergence and growth. Our results are contradictory with some researchers who found no effect of soil amendment with hydrogel on emergence and early seedling growth in different species (Ingram andYeager 1987, Akhter et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The Any two means not sharing a common letter differ significantly at P ≤ 5% level findings of the study are supported by the earlier work done by Woodhouse and Johnson (1991) who also reported the improved emergence rate and percentage by soil treated with hydrogel. Yang et al (2008) studied a novel soil stabilizer based on poly-amino acid polyaspartic acid (PASP) and its copolymer which was modified with xanthan gum (XG) and concluded that the polymer had a positive influence on seed emergence and growth. Our results are contradictory with some researchers who found no effect of soil amendment with hydrogel on emergence and early seedling growth in different species (Ingram andYeager 1987, Akhter et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These hydrogels can swell and hold a fraction of water within their networks. [1][2][3] Due to their material properties, hydrogels are widely used in the food industry, 4,5 tissue engineering, 6,7 drug delivery systems 8,9 and biomedical engineering. 10 Various types of natural and synthetic polymers have been used as microspheres including agarose, 11,12 alginate, 13 collagen, 7 and polyethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…This avoids unnecessary expenses and minimizes the environmental impacts2 caused by overuse of fertilizers in the plantations. Therefore, biodegradable hydrogels have received much attention from the agricultural sector in recent years, such as: controlled‐extended release of agricultural inputs,3–6 soil conditioners,7, 8 and erosion control 9. The use of conditioners has contributed to increase the water retention capacity in the soil, reducing the irrigation frequency, minimizing costs, and helping to improve the yield in cultures 7.…”
Section: Introductionmentioning
confidence: 99%